A whiteheadi metafizika megjelenése három fallácia fényében - Herth, Ákos (Kultúratudományi Szemle, 2024)
Whitehead and the method How can we interpret the emergence of Whitehead's metaphysical and cosmological project on the map of 20th-century philosophy after Kant's critical turn? How can this project be related to Whitehead's contemporary philosophical tendencies, such as the pragmatist movement that was developing in America? This paper assumes a fundamental link between the two questions, namely that it is necessary to clarify the methodological reflections that define their philosophies in interpreting Whitehead and the pragmatists, including William James. In Whitehead’s case, this also means that the goal of metaphysics and cosmology can only be understood as a systematic elaboration of the method. And for Whitehead, this constructing process (of the method) is the main task of speculative philosophy.